2018
DOI: 10.1007/s00109-017-1618-1
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients

Abstract: Genes involved in the neuronal biological process are enriched in nasopharyngeal carcinoma. Overexpression of NgR3 correlates with poor prognosis of nasopharyngeal carcinoma. NgR3 promotes NPC cell migration by downregulating E-cadherin. NgR3 promotes NPC cell polarity and enhances the formation of NPC cell pseudopodia by activating FAK/Src pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…Indeed, Jin et al (2016) demonstrated that Nogo-A was able to inhibit the migration and invasion of human malignant glioma cells via the downregulation of RhoA-cofilin signaling. On the contrary, NgR3 seems to induce nasopharyngeal carcinoma cell migration by activating focal adhesion kinase (FAK) ( He et al, 2018 ).…”
Section: Structure Of P75 Ntr and Binding Partnersmentioning
confidence: 99%
“…Indeed, Jin et al (2016) demonstrated that Nogo-A was able to inhibit the migration and invasion of human malignant glioma cells via the downregulation of RhoA-cofilin signaling. On the contrary, NgR3 seems to induce nasopharyngeal carcinoma cell migration by activating focal adhesion kinase (FAK) ( He et al, 2018 ).…”
Section: Structure Of P75 Ntr and Binding Partnersmentioning
confidence: 99%
“…The pathogenesis of NPC is complicated, including the Epstein-Barr virus (EBV) infection, carcinogen hazards and individual susceptibility (1,4). In clinic, NPC exhibits low differentiation and high rates of metastasis compared with other types of cancers (5)(6)(7). Although chemotherapy and radiotherapy are used, the treatment efficacy for NPC is still unsatisfactory due to the local recurrence and distant metastasis (5,8).…”
Section: Introductionmentioning
confidence: 99%
“…In clinic, NPC exhibits low differentiation and high rates of metastasis compared with other types of cancers (5)(6)(7). Although chemotherapy and radiotherapy are used, the treatment efficacy for NPC is still unsatisfactory due to the local recurrence and distant metastasis (5,8). Therefore, it is important to understand the molecular mechanisms of NPC.…”
Section: Introductionmentioning
confidence: 99%
“…The cell surface receptors NG1 (RTN4R) and NG3 (RTN4RL1) also interact directly with specific CS‐GAGs, and CS‐E has been shown to compete for NG1 and NG3 binding (26). Over‐expression of NG3 has been linked to poor prognosis and increased metastasis in other cancers (60). Treating F98 cells with surfen significantly reduced expression of multiple CSPG receptor proteins, including LAR and RAGE.…”
Section: Discussionmentioning
confidence: 99%